1992
DOI: 10.1111/j.1440-169x.1992.00479.x
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenesis in Transgenic Mice Expressing Bovine Cellular Retinoic Acid‐Binding Protein

Abstract: Transgenic mice with ectopic expression of bovine CRABP under the control of the human metallotheionein IIA promoter have shown a variety of pathological consequences. Expression of the transgene has been detected in most of the tissues examined, including heart, lung, liver, spleen, kidney, intestine, testis, and ovary, except pancreas. Two independent lines have been able to produce normal non‐transgenic F1 animals of both sexes but only female transgenic progenies. All of these F1 female transgenic animals … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

1994
1994
2016
2016

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…In transgenic mice ectopically expressing this protein, a variety of pathological consequences have been observed, which mimic the outcome of hypovitaminosis A in animals (Wei et al, 1992). Thus, it is possible that fine-tuning regulatory mechanisms for CRABP-I gene are needed for its expression regarding the level, timing, and inducibility.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In transgenic mice ectopically expressing this protein, a variety of pathological consequences have been observed, which mimic the outcome of hypovitaminosis A in animals (Wei et al, 1992). Thus, it is possible that fine-tuning regulatory mechanisms for CRABP-I gene are needed for its expression regarding the level, timing, and inducibility.…”
Section: Discussionmentioning
confidence: 99%
“…Cellular retinoic acid binding protein-I (CRABP-I) is one of the cytosolic binding proteins (Chytil and Ong, 1984) for retinoic acid (RA). Based on studies of its expression patterns in embryos (Dolle et al, 1990;Wei et al, 1991) and the phenotypes associated with an alteration in its level of expression (Boylan and Gudas, 1991;Wei et al, 1992), it is proposed that this protein may be involved in modulating intracellular RA concentration through a trapping mechanism. Based upon data showing its ubiquitous expression in animals (Kato et al, 1985) and the feature of its promoter sequence (Wei et al, 1990), this gene has been characterized as a housekeeping gene.…”
mentioning
confidence: 99%
“…, such cells are more resistant to RA induction of gene expression [10–12]. Consistent with the notion that binding to CRABPI reduces the cellular availability of RA for general growth, studies in transgenic mice showed that globally over-expressing CRABPI produced specific pathologies in growth and reproduction, as well as abnormalities of the liver and spleen [27, 28]. In contrast, mutating CRABPI (specifically, with regard to its RA-binding affinity) eliminated its ability to desensitize the response of cells to RA [12].…”
Section: Regulation Of the Crabpi Genementioning
confidence: 83%
“…Although mice deficient in this gene seemed normal phenotypically, several studies showed that overexpression of this gene altered cellular differentiation (20) or the expression of certain developmental genes (21). Thus, the absence of this gene was not devastating to animal survival, but overexpression of this protein affected cell differentiation in both transgenic mice and cell cultures.…”
Section: Discussionmentioning
confidence: 99%
“…However, it was demonstrated in transgenic mice (20) and embryonal carcinoma cells (21) that elevated CRABP-I expression was associated with abnormal cellular differentiation and RA-responsive gene expression. It was also shown in embryonic palate cells that the expression of RAR ␤ , transforming growth factor ␤3, and tenascin was altered as a result of introducing anti-crabp-I oligonucleotides into the cultures (22).…”
mentioning
confidence: 99%